SOLON BORGES DOS REIS LIBRARY RELEVANCE AND POTENTIALITIES OF THE ACHIEVES FOR THE HISTORY OF THE BRAZILIAN EDUCATION - Souza, Rosa Fatima de [UNESP] (Univ Fed Sao Paulo, Dept Education, 2018)
The text presents a reflexion on the peculiarities of the Solon Borges dos Reis Library and its relevance to the research in the area of the History of Education. Starting from the autobiographic perspective, it highlights the contribution of this institution's collection of documents to the writing of the history of primary, secondary and rural school education in the state of Sao Paulo. The text stresses the importance of the conservation of this library as an institution for the memory of education as well as pointing out the possibilities of new investigations/ researches using this collection of documents.
Keywords: Solon Borges dos Reis Library; sources of information for the History of Education; education heritage